2016
DOI: 10.1007/s00330-016-4247-0
|View full text |Cite
|
Sign up to set email alerts
|

Morphological imaging and T2 and T2* mapping of hip cartilage at 7 Tesla MRI under the influence of intravenous gadolinium

Abstract: • Hip cartilage T2 values correlate highly before and after gadolinium at 7 T • Hip cartilage T2* values correlate highly before and after enhancement at 7 T • Morphological hip cartilage imaging benefits from intravenous gadolinium at 7 T • The delineation of acetabular and femoral cartilage can be improved by gadolinium • Morphological and quantitative sequences including dGEMRIC can be combined as a one-stop-shop examination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 38 publications
0
17
0
Order By: Relevance
“…We calculated the Contrast ratio (C) between the different 3D high resolution sequences, based on the absolute value of signals difference between cartilage in three ROI's (Anterior, median and posterior) and bone or meniscus divided by the sum of both signals intensities [14]. To compare SNR between sequences, ROI's were placed in the different cartilage regions to measure the signal intensity and in the background of the image to measure the Standard Deviation (SD).…”
Section: Images Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…We calculated the Contrast ratio (C) between the different 3D high resolution sequences, based on the absolute value of signals difference between cartilage in three ROI's (Anterior, median and posterior) and bone or meniscus divided by the sum of both signals intensities [14]. To compare SNR between sequences, ROI's were placed in the different cartilage regions to measure the signal intensity and in the background of the image to measure the Standard Deviation (SD).…”
Section: Images Analysismentioning
confidence: 99%
“…The differences between 3D sequences are mostly related to the timing of the gradient pulses, the radio frequency excitation pulses and the measurement of echoes which leads to a Biomedical Research 2018; 29 (14): 2963-2970 different contrast between tissues. In order to use 3D sequence as routine sequence in the place of the three 2D sequences in different planes, the acquisition time of the 3D sequences should not exceed too much the timing of all three 2D sequences together.…”
Section: Introductionmentioning
confidence: 99%
“…In a pilot study by Nieminen et al, however, no effect of contrast agent on T2 relaxation times was found in three volunteers using a similar dGEMRIC protocol at 1.5 T 14 . Similarly, a recent study with 11 healthy volunteers found no relevant influence of intravenous gadolinium on T2 relaxation time of hip cartilage at 7 T 15 . A limitation of our study is that it was not powered sufficiently to exclude a possible effect of the dGEMRIC protocol elements based on the 95% confidence interval.…”
Section: Discussionmentioning
confidence: 82%
“…As the 8Tx/Rx body array, which served as the standard of reference in this work, has already been used in a broad variety of clinical 7T MRI investigations, [32][33][34][35][36][37][38][39][40] the improved performance of the new combined array holds great promise for 7T UHF body MRI, increasing either the spatial resolution of these examinations or speeding up the acquisition time through use of higher parallel imaging factors. Imaging results in the pelvis of a female volunteer showed high homogeneity at a very high resolution of 0.68 9 0.68 9 0.68 mm³, which was achieved within less than 10 min acquisition time.…”
Section: Discussionmentioning
confidence: 99%